Association between maternal dental periapical infections and pregnancy outcomes: results from a cross‐sectional study in Malawi. Issue 11 (18th August 2015) - Harjunmaa, Ulla; Järnstedt, Jorma; Alho, Lotta; Dewey, Kathryn G.; Cheung, Yin Bun; Deitchler, Megan; Ashorn, Ulla; Maleta, Kenneth; Klein, Nigel J.; Ashorn, Per
Abstract Objectives Maternal infections are associated with intrauterine growth restriction (IUGR) and preterm birth (PTB). Dental infections are common in low‐income settings, but their contribution to adverse pregnancy outcomes is unknown. We studied the epidemiology of dental periapical infections among pregnant women and their association to foetal growth restriction and the duration of pregnancy in a rural sub‐Saharan African population. Methods This was a cross‐sectional study on the association between maternal dental periapical infections and birth outcomes, in Malawi, Africa. We assessed oral health clinically and radiologically among recently delivered women with known duration of pregnancy and measured birthweight (BW), length and head circumference of their infants. Results Of 1024 analysed participants, 23.5% had periapical infections. Mean duration of pregnancy was 39.4 weeks, BW 2979 g and length 49.7 cm. Women with periapical infection had mean (95% CI) pregnancy duration 0.4 weeks (0.1–0.8) shorter and delivered infants with 79 g (13–145) lower BW and 0.5 cm (0.2–0.9) shorter neonatal length than women without periapical infection. The incidence of PTB was 10.0% among women with periapical infection and 7.3% among those without (adjusted difference 3.5%, 95% CI −1.1–8.1%). Corresponding prevalences for stunting were 20.9% and 14.2% (adjusted difference 9.0%, 95% CI 2.7%–15.2%). The population‐attributable risk fraction attributable to periapical infection was 9.7% for PTB and 12.8% for stunting. Conclusions Periapical infection was associated with shorter pregnancy duration and IUGR in the study area; interventions addressing this risk factor may improve birth outcomes in low‐income settings.